De Novo transcriptome combined with physiological analyses revealed key genes for cadmium accumulation in Zhe-Maidong (Ophiopogon japonicus) - Zhao, Qian; Li, Qing; Lin, Shuting; Hou, Ruijun; Liu, Jianying; Tao, Yachen; Li, Ye; Zhou, Yifeng; Ye, Zihong; Yu, Xiaoping; Huang, Jun (Frontiers in Plant Science, 2022)
Cadmium (Cd) is a toxic heavy metal that severely threatens safe food production. Zhe-Maidong, a well-known Chinese traditional herbal medicine, is susceptible to Cd stress. To investigate the characteristics of Cd transformation and distribution of Zhe-Maidong root responding to Cd stress, Zhe-Maidong seedling growth in Cd-contaminated and uncontaminated soil was conducted for 90 days. The enrichment factor (EF) value in the root was four times that of the leaves, indicating that the root has a high ability to absorb and accumulate Cd. The Cd2+ were mainly distributed in the root hair and the epidermis in both roots and leaves, revealing that the epidermal cells of roots may collect Cd2+ and also have an outstanding role in Cd2+ uptake. Under hydroponics, three different concentrations of Cd were tested using RNA sequencing. A total of 50 DEGs involved in Cd translocation and accumulation were identified. Among these DEGs, ANN, ABCC2/4, HMA1-5, and CCX gene expression were positively correlated with EF-root, EF-leaf, EF-total, Cd-leaf, Cd-root, and Cd-plant, indicating their role in Cd transport and accumulation under Cd-stress. These data could be helpful in uncovering the Cd accumulation characteristics in Zhe-Maidong, as well as provide a bioinformatic foundation for investigations on finding gene functions and the screening of candidate genes related to Cd accumulation.